Reforma a la ley de seguridad pública y del estado en cuanto a la complementariedad de acciones de las fuerzas armadas a la Policía Nacional - Tingo Guadalupe, Ángel Álvaro (2015)
Both the armed forces and police missions are clearly marked in the Constitution. Article 158: "internal protection and maintenance of public order are custodial functions of the State and responsibility of the national police national". The sentence word according to the dictionary of the Royal Academy of the Spanish language: "Own and peculiar singularly someone or something, and not another", this perfectly explains the police mission Not only that it is violating the Constitution, but other laws, namely the law of public security and the State (Art. 35), which says that you a time that the Government has declared a State of emergency and therefore, the mobilization of forces armed., they will act in support of the police It is worth mentioning that, ever the military have been beyond the control of drug trafficking, organized crime, human trafficking, weapons, fuels, etc. The armed forces have collaborated in intelligence work to prevent and neutralize criminal activities; In addition, permanently performed operations area, maritime interdiction and surveillance of borders, especially in the North The law of public security and the State gives a new authority to the Executive, the reforming was approved as well: "Art-35 complementarity of actions of the national police forces.-in order to protect the internal protection, maintenance and control of public order and public safety, the armed forces can support to complement operations which in this matter to the national police." "For this purpose, the Ministers responsible for national defense and the Interior, will coordinate the opportunity and the intervention of the forces under his command level, establishing policies and protocols that are required". I.e. is given to the Executive, the freedom to benefit at all times and under all conditions of the collaboration of the armed forces, which can cause serious consequences in the future. Urgent reform to the law of public security and the State as regards the complementarity of actions of the armed forces to the national police, in terms of internal security, singularizando the reasons by which the armed forces cooperate with State agencies, including the national police in the maintenance of public order and public security is therefore required